Penerapan PSAK 73 atas Profitabilitas, Struktur Modal dan Tangibility pada Perusahaan - Andreas Paskalis Ginting; Made Dwi Cahaya Permana; Amrie Firmansyah (Universitas Prasetiya Mulya, 2022)
This study examines the impact of applying lease accounting before and after implementing PSAK 73 in Indonesia. PSAK 73 is the adoption of IFRS 16, which took effect on January 1, 2020. This study uses a quantitative method approach using secondary data in the form of data and information sourced from the annual financial reports of 52 companies in the infrastructure sector listed on the Indonesia Stock Exchange in 2019 and 2020. Data research was obtained from Indonesia Stock Exchange (IDX). The comparison focus before and after the implementation of PSAK 73 is profitability, capital structure, and tangibility. Testing the hypothesis in this study used a paired sample t-test for paired data. This study concludes that applying PSAK 73 does not result in differences in the profitability, capital structure, and tangibility of infrastructure companies in Indonesia.